Jenis Pakan Dan Kebiasaan Makan Ayam Buras Pada Sistem Pemeliharaan Ekstensif Di Lingkungan Rumah Tangga - Pamungkas, Aditya; Nepa, Juliana Monika (CV. SINAR HOWUHOWU, 2026)
This study aims to identify the profile of natural feed sources and domestic waste, as well as to analyze the dietary adaptation patterns of native chickens in response to limited conventional feed inputs in Baumata Village, a semi-arid region of East Nusa Tenggara (NTT). The method employed was direct field observation (case study) to map feed types and poultry feeding behavior. The results indicated that the identified feed sources were categorized into three main groups: plant-based domestic waste (leftover rice and tuber peels) as the primary energy source, natural feed (termites, insect larvae, and young leaf shoots) as sources of protein and fiber, and natural supplements (surface water and grit) to support digestion. Native chickens exhibited adaptive responses through increased scavenging duration (6–8 hours per day) during the morning to mitigate heat stress and cover nutritional deficits. Although this system minimizes production costs, the lack of bone residue in household waste in Baumata Village potentially leads to mineral deficiencies (Ca and P), which may hinder growth and eggshell quality. It is recommended to implement mineral supplementation based on local potential and develop alternative protein sources from insects (BSF maggots) to maintain sustainable native chicken productivity in dryland areas.